Stabilisasi Tanah Gambut Dengan Geopolimer Hibrid Abu Terbang Dan Pasir - Wibisono, Gunawan; Azizi, Wildan; Putra, Agus Ika; Satibi, Syawal; Olivia, Monita (Universitas Andalas, 2025)
Peat soil has high water content and compression, and low bearing capacity. Peat soil stabilization is carried out to increase the bearing capacity, increase the density and strength of the soil. Geopolymer material is one of the materials for soil stabilization derived from basic materials activated with activator solutions such as sodium hydroxide and sodium silicate. This study aims to examine the unconfined compressive strength, average water content, and dry density of peat soil stabilized with a hybrid geopolymer mixture of fly ash and sand. The parameters studied were NaOH molarity of 10M, 12M, and 14M, and silicate modulus (Na2SiO3/NaOH ratio) of 1.5; 2.0; and 2.5. The results of the study showed that the highest unconfined compressive strength was obtained for a mixture with a silicate modulus of 2.5 (GP-12M-Ms2.5), which was 23.68 kPa at 28 days. Unconfined Compressive Strength (UCS) testing was conducted after the samples were cured for 7, 28, and 56 days. The unconfined compressive strength of the GP-14M-Ms2 mixture with a molarity of 14M was 23.68 kPa at 28 days. This is due to the geopolymerization reaction that releases OH- ions to dissolve silica and alumina in fly ash, and the silicate modulus (Ms) can increase the pH of the geopolymerization and bind soil particles better. The highest dry soil content was produced by the GP-12M-Ms2.5 mixture for 7, 28, and 56 days. Sand used in peat soil stabilization can help increase density because it can fill soil cavities.